2011
DOI: 10.1098/rsta.2011.0096
|View full text |Cite
|
Sign up to set email alerts
|

Confined dynamics of a single DNA molecule

Abstract: The effect of a slit-like confinement on the relaxation dynamics of DNA is studied via a mesoscale model in which a bead and spring model for the polymer is coupled to a particle-based Navier-Stokes solver (multi-particle collision dynamics). The confinement is found to affect the equilibrium stretch of the chain when the bulk gyration radius is comparable to or smaller than the channel height and our data are in agreement with the (R g,bulk /h) 1/4 scaling of the polymer extension in the wall tangential direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…However, it may be possible to make progress using mesoscopic, explicit fluid algorithms for confined systems, such as Dissipative Particle Dynamics (DPD) [116118] or Multi-Particle Collision Dynamics (MPCD) [119]. Both methods have been used for modeling confined polymers [56,120122]. …”
Section: Discussionmentioning
confidence: 99%
“…However, it may be possible to make progress using mesoscopic, explicit fluid algorithms for confined systems, such as Dissipative Particle Dynamics (DPD) [116118] or Multi-Particle Collision Dynamics (MPCD) [119]. Both methods have been used for modeling confined polymers [56,120122]. …”
Section: Discussionmentioning
confidence: 99%
“…Recent coarse-grained simulations studies have found good agreement with the predictions for blob-to-deflection transition and the scaling law dependences in nanochannels. , MC studies have examined the conformation and the free energy of DNA in strong confinement. ,,, In Q1D nanochannels, a transition in the chain relaxation dynamics is also found in experiments and coarse-grained simulations of DNA. ,, In Q2D nanoslits, it is less clear whether a qualitative change of chain properties occurs, as slit confinement does not inhibit long wavelength collective chain motion. Prior simulation studies have probed the chain property dependences for slit heights larger than the Kuhn length, , but the coarse-grained flexible polymer model for DNA prevented investigations in the H < P regime. To better understand the conformation and dynamics of confined DNA molecules in nanoslits, coarse-grained dynamics simulations are performed to study how R ∥ and t relax depend on H in nanoslits.…”
Section: Introductionmentioning
confidence: 99%
“…Connement affects also the chain dynamic properties as chain relaxation slows down with connement. 28,31 Aware of this effect, we performed extensive simulations to attain the equilibrium properties. One of the indications of reaching equilibrium is shown in the master plot in Fig.…”
Section: Excluded Volume Regimementioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] They present an efficient, nondestructive, and simple way of DNA manipulation and characterization when determining structural details in nano-and microuidic experiments. 9,10 In order to understand the structural and dynamic properties of a single chain conned in a channel and slit a great deal of theoretical, [11][12][13][14] experimental, 1,2,8,10,15 and simulation [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] studies have been published. The studies have shown that the chain relaxation slows down upon increasing the connement.…”
Section: Introductionmentioning
confidence: 99%